Effect of anti-interleukin-5 antibody on development of vasculitis in an ovalbumin-induced eosinophilic vasculitis mouse model - Kageyama, Kiyoto; Kikuchi, Eri; Hoshino, Nao (Frontiers in Pharmacology, 2025)
BackgroundEosinophilic granulomatosis with polyangiitis (EGPA) is a rare and intractable chronic disease. Glucocorticoids are the mainstay of treatment for EGPA. The drugs that target interleukin (IL)-5 signaling have also been marketed or developed in recent years. While no animal model can completely recapitulate EGPA, the ovalbumin (OVA)-induced eosinophilic vasculitis mouse model exhibits pathological similarities in the lungs. However, the effect of an anti-IL-5 drug has not yet been investigated using this model. This study used the OVA-induced eosinophilic vasculitis model to evaluate and characterize its usefulness, focusing on the effects of an anti-IL-5 antibody.MethodsFemale C57BL/6NCrSlc mice were intraperitoneally immunized on days 0 and 14 with OVA adsorbed onto an aluminum gel. From days 26–32, the mice were exposed to aerosolized 1% OVA daily for 1 h. Anti-IL-5 antibody or vehicle was injected intravenously or intraperitoneally once on the first day of aerosol exposure (day 26). On day 33, the eosinophil and lymphocyte counts in the blood and bronchoalveolar lavage fluid (BALF) were measured. Lung specimens were used to assess the vascular lesions formed in the pulmonary arteries. Plasma cytokine levels were measured on day 28.ResultsThe anti-IL-5 antibody significantly reduced eosinophil counts in the blood and BALF. In contrast, it did not inhibit the lymphocyte counts in BALF or vascular lesion formation. The anti-IL-5 antibody significantly blocked the plasma level of IL-5 on day 28. However, the levels of other cytokines (i.e., IL-2, IL-6, tumor necrosis factor-α, granulocyte-macrophage colony-stimulating factor, interferon-γ, IL-12, IL-4, IL-13, and IL-17) were not altered.ConclusionIn the investigated model, lymphocyte infiltration in lung tissue and cytokines other than or in addition to IL-5 were suggested to have contributed to the development of vasculitis. IL-5 signaling has a potential impact on EGPA pathogenesis via a different mechanism or in addition to the mechanism demonstrated in the OVA-induced eosinophilic vasculitis mouse model. The model may be useful for drug discovery targeting both eosinophilic and non-eosinophilic aspects of EGPA pathogenesis.